Revitalizing Quality Control Circle Program In A Hibernate Line Production PT.Toyota Boshoku Indonesia - Ismatulloh Ismatulloh; Fathurohman Fathurohman (Proceeding International Pelita Bangsa, 2023)
In an effort to increase customer trust PT TBINA regularly conducts QCC activities to analyze problems that exist in the field. However, in its application, this activity is not easy to carry out in each department, for the example is the Seat Assembly which sends an average of 1 group to represent 145 employees in the TBINA internal competition for the 2017-2019 period. The number is the same as the Needle Punch line but only consisting of 12 members, different with the Welding line which can sent 12 groups of 122 members.. This study aims to increase QCC activity in the Seat Assembly line. The method used in this study is the QCC analysis method. Revitalization is carried out through a leadership approach by conducting guidance and training both for employees and for leaders, grouping employees based on age and years of service, setting activity targets, making repair and improvement plans as well as evaluating and standardizing.After the QCC activity was carried out, there was an increase in operator knowledge of QCC, this encouraged active activities which can be seen in the QCC competition in 2023 where the line seat assembly can send 9 groups to represent 100 employees. QCC also has a positive impact on the achievement of work quality and productivity in the seat assembly production line.